The dynamics of songbird ownership and community interconnectedness in Singapore. Issue 4 (28th December 2022) - CHIOK, WEN XUAN; LEE, REBECCA Y. Y.; LEE, JESSICA G. H.; JAIN, ANUJ
Summary: The practice of keeping birds is a long-held tradition in South-east Asia, including in Singapore. Beyond market surveys that have documented Singapore's sizeable bird market, there is a compelling need to understand the underlying drivers of demand for songbirds, and how these are influenced by social factors. We conducted semi-structured surveys of 114 songbird owners in Singapore, so as to determine their behaviour, demography, and preferences for owning songbirds and mapped Singapore's songbird trade network. Forty-four percent of respondents reported to not prefer either wild-caught or captive-bred birds and another 37% preferred captive-bred birds. Over half (51%) did not think that there were any differences in the singing capabilities of the songbird from either source. Influence from family members and close contacts were cited as the most influential motivational factor for bird-keeping. The majority of respondents were middle-aged (77% aged 40 and above), and two-thirds (67%) were of Chinese ethnicity. Purchasing power and socio-economic status were not deemed to be strong considerations for owning songbirds. Neither was songbird ownership regarded as a status symbol, in contrast to parrot ownership in Singapore. Instead, social factors played influential roles in the songbird community, shaping the way owners gather, interact, and trade at bird shops and bird cage hanging spots. This study offers novel insights into the motivations underlying songbird ownership and its complex community linkages. We advocate for conservation interventions to target specific demographic groups that are embedded and influenced by communities so as to promote sustainable trade in songbirds.